THE PATTERNS OF CODE SWITCHING AMONG YOUTUBERS - ADI PRABOWO, YUDISTIRA (LANGUAGE HORIZON, 2018)
Abstract Code switching is the sociolinguistic case, which is study about the language used among the society. This study analyzes the use of Code-Switching among youtubers. Code Switching in youtube is usually done by people who have an experience and skills in abroad or people who use English as their second language. It has function in communication, such as for humor, bonding and dampening directness. This study uses qualitative method to involve people experience, and exploring a new area where issues are not yet understood or properly identified. The result of this study shows that the use code switching among youtubers are uttered to express speakers opinion and feelings, to reiterate or repeat the messages clearer and understood, and to entertain people. The main conditions youtubers switch the language because of their own environment both family and community are involve to their language behavior. Keywords: sociolinguistic, bilingualism, code switching